HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KETEPATAN SMASH PADA PEMAIN BULU TANGKIS GALAXI TANJUNG UBAN - Iwann Kusnaidi; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, The purpose of this study was to determine the relationship of explosive power leg muscle with the precision of the Badminton Players galaxy smash Tanjung Uban.Jenis correlational studies that compare the results of measurements of two different variables in order to determine the degree of association between these variables. As the independent variable (X) is ekplosive limb muscle power while the dependent variable (Y) is the precision of the Badminton Players galaxy smash In Tanjung Uban. Based on the research that has been conducted against the explosive power leg muscle with the precision of Smash In Badminton Players galaxy Tanjung Uban, to determine the extent of the relationship given by the explosive power leg muscle with the precision of badminton smash obtained r = 0.566, including the category